Heavy oil exposure suppresses antiviral activities in Japanese flounder Paralichthys olivaceus infected with viral hemorrhagic septicemia virus (VHSV). Issue 124 (May 2022) - Song, Jun-Young; Kitamura, Shin-Ichi; Oh, Myung-Joo; Nakayama, Kei
Abstract: A combined treatment of heavy oil (HO) exposure and virus infection induces increased mortality in Japanese flounder ( Paralichthys olivaceus ). In this study, we addressed how HO exposure affects the immune system, especially antiviral activities, in Japanese flounder. The fish were infected with viral hemorrhagic septicemia virus (VHSV), followed by exposure to HO. We analyzed virus titers in the heart and mRNA expression in the kidney of surviving fish. The virus titers in fish exposed to heavy oil were higher than the threshold for onset. The results suggest that HO exposure may allow the replication of VHSV, leading to higher mortality in the co-treated group. Gene-expression profiling demonstrated that the expression of antiviral-activity-related genes, such as those for interferon and apoptosis induction, were lower in the co-treated group than in the group with VHSV infection only. These results helped explain the high virus titers in fish treated with both stressors. Thus, interferon production in the virus-infected cells and apoptosis induction by natural killer cells worked normally in the VHSV-infected fish without HO exposure, but these antiviral activities were slightly suppressed by HO exposure, possibly leading to extensive viral replication in the host cells and the occurrence of VHS. Highlights: Japanese flounder were infected with VHSV, followed by exposure to heavy oil. 50% of the fish treated with both VHSV and heavy oil had died, whereas there was no mortality in the single stressor groups. Energy production pathway was a target of each treatment. Antiviral activity-related genes including granzyme and perforin were up-regulated by VHSV infection. Antiviral activities might be less sufficient under the heavy oil exposure.